PAN-ASIAN BEAUTY IDEOLOGY IN INDONESIAN SKINCARE PRODUCTS ADVERTISEMENTS: CRITICAL DISCOURSE ANALYSIS - Muhammad Hafiz Kurniawan; Neidya Fahma Sunendar; Juwintan Juwintan; Liana Snytsar (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
Social media has changed the people perspective about beauty because it shapes beauty standard by giving exposure to particular body shape and skin tone. This research aims to investigate the ideology in the concept of beauty in local brand of skincare products in Indonesia via Instagram. Those two local brands are chosen because it shows how different ideologies are starting to be contested: “whiteness’ and ‘local’ beauty. This concept cannot be ignored because it is rooted in imperialism and colonialism. To reveal the ideology, this research began with the analysis of visual and verbal texts in Instagram posts from two official accounts, Kezia Skincare and Votre Peau. This case study uses Critical Discourse Theory proposed by Jäger & Maier and then supported by theories developed within social semiotics. The data in this research were collected by applying four steps adopted from Bezemer and Jewitt and in analyzing the data this research focuses on the discourse fragments to reveal the ideological statements. Linguistic and non-linguistic features are used intersemiotically to strengthen the message of ‘whiteness’ and ‘brightness’ beauty is within the customer reach. Although, one of beauty products has promoted the ‘local’ beauty, the consistency is still questioned because whiteness beauty ideology and the pan-Asian beauty still leaves the trace in representing the beauty thorough process types, metaphors, pathos and images.